The innovation in the elements of the marketing mix and its impact on the preferences of the Algerian consumer for local and foreign smartphones. - Mohammed Lamine, Otmani; Mahmodi, Ahmed (Dirassat Journal Economic Issue, 2023)
This study aims at knowing the extent of the impact innovation in the elements of the marketing mix on the preferences of Algerian consumers for local and foreign smartphones based on a hypothetical model that takes the nature of the relationship between innovation in the elements of the marketing mix and consumer preference for the local and foreign smartphone. Two basic hypotheses were built from which a set of sub-hypotheses emerged. We concluded that there is a strong correlation and impact between innovation in the elements of the marketing mix and consumer preferences for smart phones. We reached a set of conclusions and recommendations that highlight the importance of innovation in the elements of the marketing mix in building a preferential base, starting from the sample of this study and arriving at the study community, which is the Algerian market and employing all its elements to make the local product reach the largest possible market segment.